Position of the Premises in the Authentic Deed Made by the Notary - SUGIANA, Surya; WESNA, Putu Ayu Sriasih; AGUNG, Anak Agung Istri (Journal of Political And Legal Sovereignty, 2024)
Purpose:This research aims to analyze and examine the premises' position in an authentic deed made by a notary. It is motivated by the absence of explicit regulations regarding the premise in the Notary Position Law, even though the premise plays a vital role in explaining the background and intention of doing the deed. Legal uncertainty related to the premise can cause legal uncertainty in the practice of notary, especially in proving in court in the event of a dispute.Methodology:This research uses normative research methods with legislative approaches and conceptual approaches. The data used consisted of primary legal materials in the form of laws and regulations and secondary legal materials in the form of literature and scientific journals. The data collection technique was carried out through a literature study and analyzed qualitatively using the legal interpretation method with deductive reasoning.Findings:The results of the study show that although the position of the premise is not expressly regulated in Article 38 of the Law on the Position of Substitute Notary regarding the anatomy of the deed, in practice, notary, the premise is still used and considered necessary. The premise is generally laid after the comparison and before the content of the deed, serving as an explanation of the background, facts, and reasons for the parties to do the deed. The premise also helps notaries explore the material truth so that the deed can provide maximum legal protection.Implication:This research implies a need for a regulatory update in the Notary Office Law to explicitly regulate the position of the premise in the anatomy of an authentic deed. This arrangement will provide legal certainty for notaries and interested parties and strengthen the function of authentic deeds as valid and perfect evidence before the law.